Challenges in the Adoption of Mobile Money Services by Mobile Phone Users in Lusaka, Zambia. - Nyika, Andrew Mweemba (Journal of Business and Strategic Management, 2024)
Purpose: This study investigates mobile money adoption in Lusaka, Zambia, utilizing a mixed-methods approach. Methodology: The study employs a mixed-methods approach to explore mobile money adoption in Lusaka, Zambia. Findings: The study uncovers several key findings regarding mobile money adoption in Lusaka, Zambia. Convenience, ease of use, and perceived security emerge as primary motivators for adoption. Conversely, lack of understanding, perceived risk, and a preference for traditional banking methods are identified as major deterrents. Interestingly, cultural factors, such as religious beliefs, play a minimal role in adoption decisions. Demographic factors, including age, education level, and income, exhibit a complex interplay with adoption rates, with younger, more educated, and higher-income individuals generally more inclined to use mobile money. Unique Contribution to Theory, Practice, and Policy: The study's findings contribute to both theory and practice in the field of mobile money adoption. They highlight the predominance of practical considerations over cultural factors in technology adoption, suggesting the need for enhanced adoption models that go beyond traditional socio-economic determinants. Additionally, the study identifies technological discomfort as a significant deterrent to adoption, indicating a need for improved digital literacy and user-friendly interfaces. Furthermore, an awareness-confidence paradox is revealed, wherein increased awareness of cyber scams negatively impacts trust in mobile money security. This suggests the importance of balancing risk education with strong security reassurances. Fee perception also emerges as a hurdle, with over 60% of respondents perceiving fees as unfair, underscoring the importance of educating users on the value proposition of mobile money services. Overall, the study offers valuable insights for strategic product and service development, regulatory and policy formulation, and initiatives aimed at advancing financial inclusion and promoting economic growth in similar urban and semi-rural settings.